Addressing Underrepresentation in Sex Work Research: Reflections on Designing a Purposeful Sampling Strategy. (June 2016) - Bungay, Vicky; Oliffe, John; Atchison, Chris
Men, transgender people, and those working in off-street locales have historically been underrepresented in sex work health research. Failure to include all sections of sex worker populations precludes comprehensive understandings about a range of population health issues, including potential variations in the manifestation of such issues within and between population subgroups, which in turn can impede the development of effective services and interventions. In this article, we describe our attempts to define, determine, and recruit a purposeful sample for a qualitative study examining the interrelationships between sex workers' health and the working conditions in the Vancouver off-street sex industry. Detailed is our application of ethnographic mapping approaches to generate information about population diversity and work settings within distinct geographical boundaries. Bearing in mind the challenges and the overwhelming discrimination sex workers experience, we scope recommendations for safe and effective purposeful sampling inclusive of sex workers' heterogeneity.